Postrzeganie przez uczniów świata wartości ich nauczycieli jako integralny składnik wychowania do wartości w szkole = Students` perception of their teachers` world of values as an integral component of education for values in school - Sałaciński, Lech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Education for values is a profound process of introducing human beings into the right issues of evaluation, developing in them proper attitudes to values, and having on them an educational impact consistent with the values both felt and recognized. Such a model of education should be a product of both parental family and school endeavors.
Keywords: uczniowie; nauczyciele; wartości; stosunki rodzic-dziecko; stosunki nauczyciel-uczeń; wychowanie; wychowanie do wartości